THE RELATIONSHIP BETWEEN SELF-EFFICACY AND SELF-CARE MANAGEMENT IN ELDERLY PATIENTS WITH HYPERTENSION AT THE ELDERLY - Wilda, Lexy Oktora; Ekwantoro, Ekwantoro; Suroso, Heri; Falentinno , Virgo; Paraswati, Mareta Deka (SYNTIFIC, 2023)
Background. One of the main strategies that can be done to improve self-care management is in terms of the patient himself increasing self-efficacy. Through self-confidence and self-motivation in their ability to implement healthy behaviors to control hypertension. This study aims to determine the relationship between Self-Efficacy and Self-Care Management in Elderly People with Hypertension at the Mangundikaran Nganjuk Elderly Posyandu. Research Method. The research design uses a correlational study with a cross-sectional approach. The population of elderly people with hypertension was 51 people, the sampling technique was total sampling. The sample of this study was 51 respondents. The independent variable is Self-Efficacy measured using the GSE questionnaire, the dependent variable is Self-Care Management using the self-care management questionnaire. Statistical tests using Spearman rank. Findings. The results of the study from 51 respondents, most of the respondents 35 (68.6%) had low Self-Efficacy. Almost half of the respondents 21 (41.2%) had good Self-Care Management. The results of the Spearman rank correlation test show p value = 0.001 (a< 0.05) H0 is rejected then, there is a relationship between Self-efficacy with Self-care management. The value of r = 0.624 which means that the direction of the relationship of this study shows a positive direction, the higher the self-efficacy the higher the self-care management. Conclusion. One of the main strategies that can be done to improve self-care management is in terms of the patient himself increasing self-efficacy. Through self-confidence and self-motivation in their ability to implement healthy behaviours to control hypertension.